"Who" should be focused? The influence of focus status on pronoun resolution. (27th August 2016) - Xu, Xiaodong; Zhou, Xiaolin
Abstract: Focus is assumed to be able to enhance the salience of a focused constituent and thereby facilitate the interpretation of a pronoun that refers to a focused antecedent relative to an unfocused antecedent. To assess how discourse‐based focus structure influences the interpretation of a pronoun and whether this process is modulated by the grammatical role of the antecedent, we conducted an ERP study in which the focus status of a pronoun's potential antecedents was manipulated by means of a wh ‐question‐answer structure. We found that, relative to those in the focused position, pronouns referring to antecedents in the unfocused position evoked enhanced positive responses in both early (180–230 ms) and late time windows (400–800 ms). Moreover, while a larger positivity was evoked by object‐referring pronouns compared to subject‐referring pronouns in the 400–800 ms time window over the right hemisphere, there was no effect of grammatical role in the 180–230 ms time window. These findings indicate that, while the initial stage of pronoun resolution is modulated by focus information assigned via a wh ‐question structure, integration of the pronoun and its antecedent into a coherent discourse representation at the later stage could be constrained by various factors, including the focus status and possibly the grammatical role of the antecedent.